Effects of magnetite nanoparticles on the thermorheological properties of carrageenan hydrogels - Daniel-da-Silva, Ana L. (2008)
The influence of magnetite (Fe3O4) nanoparticles on the rheological properties of κ-, ι- and λ- carrageenan gels has been investigated. Small amplitude oscillatory shear measurements were performed to study the effect of the presence of Fe3O4 nanoparticles with particle sizes of ca. 10 nm on the gel properties, as a function of carrageenan type, carrageenan concentration and magnetite load. The formation of Fe3O4 nanoparticles on the presence of biopolymer was observed to promote the gelation process and lead to stronger gels as indicated by an increase in the gel viscoelastic moduli and of the gelation temperature. This effect was more marked for κ-carrageenan than for ι- and λ-carrageenan and has been proposed to depend not only on Fe3O4 concentration but also on the concentration of potassium ions. A mechanism based on the combined effect of Fe3O4 nanoparticles and potassium ions was suggested, involving the adsorption of potassium ions on the negatively charged surface of the Fe3O4 nanoparticles, thus leading to an increase of the potassium ion concentration within the “carrageenan cages” containing the magnetite. This would, therefore, promote more extensive biopolymer helical aggregation, thus resulting in the formation of a stronger κ-carrageenan gel in the presence of Fe3O4, as observed. Since ι- and λ-carrageenan gels are known to be less sensitive to potassium ions concentration, the effect of precipitating Fe3O4 within these biopolymers is reduced.